2007
DOI: 10.1186/1860-5397-3-43
|View full text |Cite
|
Sign up to set email alerts
|

The tert-amino effect in heterocyclic chemistry: Synthesis of new fused pyrazolinoquinolizine and 1,4-oxazinopyrazoline derivatives

Abstract: The synthesis of novel fused heterocycles is based on reactions proceeding by the mechanism of the tert-amino effect, which generalizes cyclization of certain derivatives of 3-methyl-1-phenyl-2-pyrazolin-5-ones. Using this strategy a variety of fused heterocycles is obtained by the Knoevenagel condensation of 5-tert-amino-3-methyl-1-phenylpyrazolone-4-carboxal-dehyde 3 with active methylene compounds such as malononitrile and cyanoacetamide followed by cyclisation using anhydrous zinc chloride.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…The Reinhoudt reaction is also characteristic of five-membered heterocycles [6,26,28,30] and their fused analogs [53,54]. Thus, in 5-chloro-3-methyl-1-phenylpyrazole-4-carbaldehyde [26,28] the chlorine atom was easily substituted by secondary amines.…”
Section: -100%mentioning
confidence: 99%
See 3 more Smart Citations
“…The Reinhoudt reaction is also characteristic of five-membered heterocycles [6,26,28,30] and their fused analogs [53,54]. Thus, in 5-chloro-3-methyl-1-phenylpyrazole-4-carbaldehyde [26,28] the chlorine atom was easily substituted by secondary amines.…”
Section: -100%mentioning
confidence: 99%
“…It should be noted that all the above-mentioned reactions took place without a catalyst. However, the use of Lewis acids considerably accelerated [26,[58][59][60][61] cyclization by the tert-amino effect mechanism and made it possible to extend the applicability of the reaction [26,61]. It was also shown that using such acids as trifluoroacetic, HCl, HBr or (-)-camphorsulfonic acid allowed to cyclize the vinyl derivatives 72 containing only one withdrawing group at the double bond [57,62].…”
Section: -100%mentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, the Knoevenagel condesation about the pyrazole aldehyde as starting materials were reported. But these reactions are usually catalyzed by sodium acetate or piperidine in ethanol, [11][12][13] and the yield is low. Herein, we reported a genuienly green and mild Knoevenagel condensation containing pyrazole ring catalyzed by thiourea under microwave-assisted solvent-free conditions (Scheme I and Table 1).…”
Section: Introductionmentioning
confidence: 99%